2008
DOI: 10.2527/jas.2007-0276
|View full text |Cite
|
Sign up to set email alerts
|

Parentage identification using single nucleotide polymorphism genotypes: Application to product tracing1

Abstract: Identification of relatives using SNP markers has many possible applications. One is as a route to tracing a food product such as a cut of meat back to its source of origin by identifying the parents of the animal from which the product was derived. We develop methods for using SNP markers with maximum likelihood, allowing for the possibility of genotyping errors that would cause false exclusions by simpler methods. We use expectations of likelihood ratios to consider how gene frequencies in the parental popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…In addition to the quantity, the quality of marker data has a large impact on the performance of parentage (Marshall et al 1998;Kalinowski et al 2007;Hill et al 2008) and sibship (Wang 2004) assignment methods. To avoid false exclusions of sibship and parentage, various models of genotyping errors have been proposed and applied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the quantity, the quality of marker data has a large impact on the performance of parentage (Marshall et al 1998;Kalinowski et al 2007;Hill et al 2008) and sibship (Wang 2004) assignment methods. To avoid false exclusions of sibship and parentage, various models of genotyping errors have been proposed and applied.…”
Section: Discussionmentioning
confidence: 99%
“…According to Marshall et al (1998), a positivo LOD score means that the candidate parent is more likely to be the true parent than not the true parent. Hill et al (2008) suggested that an observed LOD score greater than 5 was strong evidence that the sire had been identified, whereas a negative LOD score gave strong evidence that the sire had not been found. In the current study, working with 80 or more SNP, all the offspring were assigned to the true father for scenarios 1 and 2.…”
Section: Thresholds For Parameters For Paternal Identificationmentioning
confidence: 93%
“…Several stndies have been carried out to evaluate the power of DNA markers for parental identification and traceability in livestock (Hayes et al, 2005;Gomez-Raya et al, 2008). The concept of parental identification was extended by Hill et al (2008) for application in product tracing, particularly in pigs. They calculated, based on simulation, that 100 to 150 SNP with minor alíele frequencies (MAF) >0.3 would be sufficient to trace a piece of meat back to the parents and to the farm of origin.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative methods, including statistical likelihood-based procedures, are also able to qualify parentage but were not explored in these data. Likelihood procedures offer an alternative methodology to this problem but still require extensive calibration for allele and genotype frequencies as well as population structure and the number of possible sires (Dodds et al 2005;Hill et al 2008). Further, principal component analysis of the SNP data can be used to identify half-sib or full-sib groups even in the absence of parental information.…”
Section: Discussionmentioning
confidence: 99%